National Research Agenda for the Prevention of Occupational Hearing Loss—Part 1 - Themann, Christa; Suter, Alice H.; Stephenson, Mark R. (Seminars in Hearing, 2013)
The mission of the National Institute for Occupational Safety and Health (NIOSH) is to generate new knowledge in the field of occupational safety and health and to transfer that knowledge into practice for the betterment of workers. Since its establishment in 1970, NIOSH has provided national and world leadership in efforts to prevent occupational hearing loss. In 1996, NIOSH established the National Occupational Research Agenda (NORA). Because occupational hearing loss is one of the most common occupational illnesses among American workers, it was identified as a priority research area, and a NORA Hearing Loss Team was established. The NORA Hearing Loss Team was composed of representatives from industry, academia, labor, professional organizations, and other governmental agencies. The team was tasked with developing a national research agenda for the prevention of occupational hearing loss. Each team member contributed to the original draft, which continued to evolve over time. The current document represents the culmination of several years of deliberation and revision with the goal of identifying needed research to prevent occupational hearing loss. This is Part 1 of the document, outlining research needs on the mechanisms and consequences of occupational exposure to noise and other ototoxicants.
Keywords: Occupational hearing loss; hearing conservation; hearing loss prevention; noise exposure